2014
DOI: 10.1523/jneurosci.1953-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Slow Oscillations during Sleep Coordinate Interregional Communication in Cortical Networks

Abstract: Large-amplitude sleep slow oscillations group faster neuronal oscillations and are of functional relevance for memory performance. However, relatively little is known about the impact of slow oscillations on functionally coupled networks. Here, we provide a comprehensive view on how human slow oscillatory dynamics influence various measures of brain processing. We demonstrate that slow oscillations coordinate interregional cortical communication, as assessed by phase synchrony in the sleep spindle frequency ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
101
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(121 citation statements)
references
References 65 publications
19
101
1
Order By: Relevance
“…In this way, spindles are nested within the slow oscillations Cox et al, 2014). A recent study confirmed the coupling of spindles with the slow oscillation and further showed that the timing of the spindles in relation to the slow oscillation was important for memory consolidation.…”
Section: Slow Waves Spindles and Ripples In Memory Consolidationmentioning
confidence: 87%
See 1 more Smart Citation
“…In this way, spindles are nested within the slow oscillations Cox et al, 2014). A recent study confirmed the coupling of spindles with the slow oscillation and further showed that the timing of the spindles in relation to the slow oscillation was important for memory consolidation.…”
Section: Slow Waves Spindles and Ripples In Memory Consolidationmentioning
confidence: 87%
“…Indeed, presenting specific cues associated with the original learning during subsequent SWS can facilitate memory performance upon awakening, for the auditory modality in rodents (Bendor and Wilson, 2012) and humans (Creery et al, 2015). In the olfactory modality, odors that were part of the learning context, when presented during SWS, memory retention of paired associate learning in humans (Rasch et al, 2007).…”
Section: Cuing In Swsmentioning
confidence: 99%
“…This "nesting" of oscillations has been shown to occur in both humans and animals (Jensen and Colgin, 2007;McGinn and Valiante, 2014), and to relate to various task-related processes (Canolty et al, 2006), including perception (Händel and Haarmeier, 2009;Voytek et al, 2010;Gross et al, 2013), cognitive control (Cohen et al, 2009;Dürschmid et al, 2013), memory (Sauseng et al, 2008;Tort et al, 2009;Axmacher et al, 2010;Belluscio et al, 2012), and emotional processing (Popov et al, 2012). Crossfrequency coupling has also been related to spontaneous activity during sleep (Cox et al, 2014) and "default-mode" resting state (Foster and Parvizi, 2012). In general, cross-frequency coupling is proposed to reflect a common, fundamental principle of how neurophysiological processes in the brain can be temporally organized across different frequency bands (Lisman, 2005;Canolty and Knight, 2010), and thus, different time scales.…”
Section: Q5mentioning
confidence: 96%
“…Recently, we introduced a simple modification to the PAC metric in an analysis of spindle-beta coupling (11-16 Hz and 20-25 Hz, respectively) in human electrophysiological sleep data (Cox et al, 2014). This method entails a linear removal of the phase clustering bias, resulting in debiased PAC (dPAC).…”
Section: Debiasing Cross-frequency-coupling: Theory and Implementationmentioning
confidence: 99%
“…We determined whether these parameters --SW phase at spindle peak and consistency --differed by group and, to test our main hypothesis, we correlated them with sleep dependent memory consolidation. (C) As a secondary analysis to confirm timing results we used the standard technique, phase amplitude coupling (PAC) [40][41][42] , which uses all spindle time points to identify the SW phase at which sigma amplitude is maximal and tests the significance of this coupling.…”
Section: Sw-spindle Coordination Analysesmentioning
confidence: 99%